THE CRITICAL THINKING SKILLS OF BIOLOGY PROSPECTIVE TEACHERS IN ECOLOGICAL PRACTICUM - Hunaepi, Hunaepi; Susantini, Endang; Firdaus, Laras; Samsuri, Taufik; Raharjo, Raharjo (Jurnal Ilmiah IKIP Mataram, 2019)
This study aims to identify biology prospective teachers’ critical thinking skills in ecological practicum at IKIP Mataram. The survey method was carried out in this study involving 100 student determined using purposive sampling technique. An essay-shaped test instrument consisting of 6 items developed by the researcher and validated by experts was used to obtain data on biology prospective teachers’ critical thinking skills. The results showed the percentage of basic clarification indikators reached 40%, basic grouping 40%, conclusion 37%, further clarification, 36%, and strategy and tactics 20%. Each of these catalysts showed ≥ 40% achievement. These results indicate that students' critical thinking skills are still in the low category so that serious handling is important to do.